Mooreonuphis bajacalifornica, a new onuphid\(Polychaeta: Onuphidae) epizoic on the thorny oyster, Spondylus princeps unicolor - León-González, Jesús Ángel de (1988)
A new onuphid polychaete, Mooreonuphis bajacalifornica n. sp. is described based on specimens recovered from the epibiota of the thorny oyster Spondylus princeps unicolor Sowerby, collected at Puerto Escondido, Baja California Sur, México. M. bajacalifornica has strap-like branchiae beginning from setiger 15-27, and cirridorm ventral cirri on seticer 1-6. Yellowish bidentate subacicular hooks begin a setiger 13-20. Setiger 1-5 possess two types of tridentate pseudoeomposite hooks, and stout simple hooks. Observations on morphological variations are presented, as well as a key to the species of Mooreonuphis known from the Mexican coast.